Modeling multi-agent systems activities through colored petri nets : an industrial production system case study - Fernandes, João M. (1998)
This paper presents and discusses an industrial production system model based on Colored Petri Nets. The model was developed in order to analyse the agent's behavior of a distributed multi-agent system oriented to the simulation of the management and control of a specific hardmetal production system plant. This effort help us to create the basis to get a more robust system with means to resist better against eventual conflict, contention or deadlock situations among system's agents. Colored Petri Nets was chosen essentially due to their ability to describe explicitly system's states and actions and for having a semantic which builds upon true concurrency.